Gender dan Orientasi Seksual Waria: Faktor Pembentukannya pada Lingkungan Keluarga - Harpan Reski Mulia (Universitas Islam Tribakti Lirboyo Kediri, 2021)
This paper specifically explores the role of the family in shaping the gender identity of shemale and how the gender of shemale refers to their sexual orientation. This research conduct in Yogyakarta with a qualitative research method. Data obtained by using interviews, observation, and documentation. The subjects in this study were six transgender people. The research data was then analyzed by referring to Miles and Huberman's opinion, namely data reduction, data presentation, and conclusions. This study shows that the family has a role in shaping the identity of transgender women, both indirectly and indirectly, namely by giving toys that are not by gender, providing bullying with the call of transgender. The family's direct role is to direct children to become transgender women because